Evaluation of Natural Gas Saving Measures in Public Educational Institutions - Volodymyr Pashkevich; Yurij Furdas; Volodymyr Craiovsky; Vasyl Zhelykh (Energy Engineering and Control Systems, 2020)
The article analyzes the data of gas consumption for the heating periods and confirms that for the actual outdoor air temperatures there is a decrease in gas consumption. Necessary heat loads and gas consumption were determined to ensure the required indoor air temperature in the premises of the educational buildings with the proposed mode of gas savings by lowering the indoor air temperature, the so-called economical mode of operation of the boiler room. The theoretical economy of gas from lowering the temperature regime is determined. To increase the accuracy of the experiment, the comparison of the amount of gas consumed was performed in terms of working and non-working periods of the day. Based on these studies, it should be noted that the actual plot can be used to determine the actual gas savings in real conditions.